Boswellic acid as a potential adjunct for bone healing after endodontic surgery: In vitro study - Ahmed A. Aldandan; Mohamed Hassan El-Kenawy; Abdullah A. Al-Sharif; Eman T. Hamam; Amany E. Badr (Wolters Kluwer Medknow Publications, 2024)
Introduction: The role of Acetyl -11-keto-β-boswellic acid (AKBA) in regulating osteoblast differentiation was recently brought to light. Therefore, the current study was designed to explore the osteogenic differentiation capability of AKBA on bone marrow mesenchymal stem cells (BMMSCs) as a potential therapeutic agent to accelerate the healing process in apicoectomy. Materials and Methods: BMMSCs were characterized by flow cytometry. Cellular viability and proliferation assays were used with different concentrations of AKBA. Cells were divided into 5 groups to test osteogenic differentiation: Group I: negative control, Group II: positive control, Group III: BMMSCs were treated with 1 μM AKBA, Group IV: BMMSCs were treated with 0.1 μM AKBA, and Group V: BMMSCs were treated with 0.01 μM AKBA. Mineralization assays and gene expression analysis were assessed, and the significance difference between groups was established at P < 0.05. Results: The flow cytometry analysis demonstrated that BMMSCs had positive expression for mesenchymal stem cell marker and negative expression for hematopoietic markers. The concentration of 0.01 μM gave significantly higher cell density than the untreated cells after 7 days (P < 0.05). Cells treated with 0.1 and 0.01 μM AKBA revealed a significantly higher ALP activity, alizarin red, and von Kossa staining than control groups (P < 0.05). High expression of osteogenic genes was detected in BMMSCs treated with 0.1 μM AKBA (P < 0.05). Conclusions: It was declared that the concentration of 0.1 μM AKBA has no toxicity on BMMSC viability and proliferation with an impact on BMMSC osteogenic differentiation. Therefore, AKBA (0.01 μM) could be used in bone regeneration during periradicular surgery.